Ongoing censorship regime (Russia) - Voidly (Voidly Global Censorship Index, 2025)
CRITICAL severity censorship detected in Russia. Data sourced from OONI.
Censorship Incident ID: RU-2025-0009. Severity: critical. Confidence: 92%